Controlling the Soliton Explosions in Fiber Lasers with Parameter Management. Issue 5 (1st November 2020) - Latas, Sofia C. V.; Ferreira, Mário F. S.
ABSTRACT: We investigate different ways of controlling the soliton explosions in passively mode-locked fiber lasers through management of the system parameters. Assuming a set of reference values for these parameters, we find that the number of soliton explosions increases with the magnitude of fiber anomalous dispersion. The soliton explosions are suppressed and the stationary pulse width is reduced for relatively low absolute values of dispersion. Similar effects can be achieved using relatively high values of the nonlinear gain. The suppression of soliton explosions is also observed for low absolute values of the nonlinear gain saturation and in situations of relatively high linear losses.